Putting the Dominican Republic on the map - Neale, Christopher M.U. (Technical Centre for Agricultural and Rural Cooperation, 2003)
Geographical Information Systems (GIS) form the basis of a new database that maps all irrigation water users on the Caribbean island and will improve water management practices.